Further development of a multimodal pushover analysis procedure for seismic assessment of bridges. - Paraskeva, Themelina S. (Earthquake engineering & structural dynamics.)
An improvement is first suggested to the modal pushover analysis (MPA) procedure for bridges initially proposed by the writers, the key idea being that the deformed shape of the structure responding inelastically to the considered earthquake level is used in lieu of the elastic mode shape. The proposed MPA procedure is then verified by applying it to two actual bridges. The first structure is the Krystallopigi bridge, a 638 m-long multi span bridge, with significant curvature in plan, unequal pier heights, and different types of pier to deck connections. The second structure is a 100 m long three span overpass bridge, typical in modern motorway construction in Europe, which, although ostensibly a regular structure, is found to exhibit a rather unsymmetric response in the transverse direction, mainly due to torsional irregularity. The bridges are assessed using response spectrum, 'standard' pushover (SPA) and MPA and finally using non-linear response history analysis (NL-RHA) for a number of spectrum compatible motions. The MPA provided a good estimate of the maximum inelastic deck displacements of bridges wherever the contribution of the first mode to the response of the bridge was relatively low.